2019
DOI: 10.1111/aji.13182
|View full text |Cite
|
Sign up to set email alerts
|

Tokishakuyakusan, a Kampo medicine, attenuates endometriosis‐like lesions and hyperalgesia in murine with endometriosis‐like symptoms

Abstract: ProblemHow are the effects of Tokishakuyakusan (TSS), a traditional Japanese medicine (Kampo) on murine endometriosis model?MethodsBALB/c mice were used for making the murine endometriosis model. Homogeneous uterus was surgically implanted with lipopolysaccharide (LPS) in peritoneal cavity. We administered 2 weeks of TSS (1.0 g/kg) orally. Upon treatment completion, we performed the hot plate test for all mice and collected blood samples before sacrifice. Then, the endometriosis‐like lesions and uteri in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although the exact mechanism behind the formation of ovarian endometrioma remains unclear, it is more likely that pieces of endometrial tissue translocate via the fallopian tubes back to the pelvic cavity and seed onto the ovarian surface, gradually forming into a cyst. During every menstrual cycle, the cyst can grow and undergo high amounts of tension, thus leading to its rupture [ 8 ]. Recent data support that approximately 1/3 of patients with ovarian endometrioma (unilateral or bilateral) complain of lower abdominal pain, which is usually induced by the endometriotic cyst rupture and irritation of the peritoneum by the thick contents of the cyst [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism behind the formation of ovarian endometrioma remains unclear, it is more likely that pieces of endometrial tissue translocate via the fallopian tubes back to the pelvic cavity and seed onto the ovarian surface, gradually forming into a cyst. During every menstrual cycle, the cyst can grow and undergo high amounts of tension, thus leading to its rupture [ 8 ]. Recent data support that approximately 1/3 of patients with ovarian endometrioma (unilateral or bilateral) complain of lower abdominal pain, which is usually induced by the endometriotic cyst rupture and irritation of the peritoneum by the thick contents of the cyst [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the formation of chocolate cysts remains unclear but is currently thought to be secondary to the following process[ 7 , 8 ]. Pieces of endometrium travel back to the pelvic cavity with menses via the fallopian tubes and are seeded onto the ovarian surface; during each cycle and under the effect of estrogen, the pieces of endometrium seeded onto the ovary bleed and gradually form into a cyst when drainage is unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that TSS ameliorated the hyperalgesia in a murine endometriosis model. 8 We analyzed the inflammatory mediators of mRNA expressions on the endometriosis lesions and uteri through the murine endometriosis model. In the uterus, TSS repressed murine Ptgs2 (COX-2 in human) mRNA expression, indicating that TSS could decrease COX-2/PG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…2b). Recently, we demonstrated that TSS ameliorated the hyperalgesia in a murine endometriosis model 8 . We analyzed the inflammatory mediators of mRNA expressions on the endometriosis lesions and uteri through the murine endometriosis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation